Restriction enzyme digestion analysis of PCR-amplified DNA of Blastocystis hominis isolates - Ithoi, Init; Foead, A.L.; Fong, Mun Yik; Yamazaki, H.; Rohela, M.; Yong, Hoi Sen; Mak, J.W. (SEAMEO Regional Tropical Medicine and Public Health Network, 2007)
Genomic DNA of Blastocystis isolates released into 0.1 Triton X-100 was suitable for amplification and yielded similar results as the genomic DNA extracted with standard kit. The specific B. hominis primers (BH1: GCT TAT CTG GTT GAT CCT GCC AGT and BH2: TGA TCC TTC CGC AGG TTC ACC TAC A) successfully produced the PCR product of about 1,770 bp with all the 7 Blastocystis isolates tested. The restriction fragment length polymorphism (RFLP) patterns yielded by 13 out of 25 restriction endonucleases showed that the 7 isolates could be grouped into 4 subgroups: subgroup-1 consisted of isolate C; subgroup-2 of isolates H4 and H7; subgroup-3 of isolates KP1, Y51 and M12; and subgroup-4 of isolate 27B05. The differences between subgroups manifested as clear-cut RFLP patterns. A common band of 230 bp was revealed by Eco R1 in all the Blastocystis isolates tested. The band of about 180 bp was revealed by Alu I, differentiated symptomatic from asymptomatic isolates of this parasite, and might indicate the pathogenicity of this parasite.